4.0 in metal forming - Questions and challenges - Hagenah, Hinnerk; Schulte, Robert Karl; Vogel, Manfred; Hermann, Jennifer; Scharrer, Hannes; Lechner, Michael; Merklein, Marion (Procedia CIRP, 2019)
The paper gives a view on perspectives for metal forming processes rising due to the industry 4.0 discussion and its consequences. The discussion starts with a view at aims pursued by introducing 4.0 into metal forming. From the results of this the needed data and required sensors are discussed as well as the potential of their introduction into current processes. At this point the processes in metal forming and their respective demands have to be taken into account as well. From here the step to the specific challenges, e.g. originating from the machine tools at hand, can be elaborated on.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Digital manufacturing system; Lifecycle; Metal forming

Additive Manufacturing of Tailored Blank for Sheet-Bulk Metal Forming Processes - Schulte, Robert Karl; Papke, Thomas; Lechner, Michael; Merklein, Marion (2020)

Analysis of fundamental dependencies between manufacturing and processing Tailored Blanks in sheet-bulk metal forming processes - Schulte, Robert Karl; Hildenbrand, Philipp; Vogel, Manfred; Lechner, Michael; Merklein, Marion (International Conference on the Technology of Plasticity, ICTP 2017, 17-22 September 2017, Cambridge, United Kingdom, 2017)
LFT Import::2019-08-05 (2232)
Keywords: Cold forming; Deep drawing; Tailored Blank

An Innovative Process Combination of Additive Manufacturing and Sheet Bulk Metal Forming for Manufacturing a Functional Hybrid Part - Merklein, Marion; Schulte, Robert Karl; Papke, Thomas (Journal of Materials Processing Technology, 2020)
The combination of additive manufacturing (AM) and forming offers new opportunities in part and process chain design. To show the potential of this process combination, a gear component with discrete tooth geometry is manufactured by powder bed fusion of metal using a laser beam (PBF-LB/M) and forming. Such gear components are manufactured conventionally in a process chain of several sheet bulk metal forming operations like orbital forming, deep drawing and upsetting. Orbital forming is used to manufacture a tailored blank to increase form filling in the subsequent forming operations. However, challenges are form filling and control of material flow. These severely affect whether the target geometry can be realized. To overcome these limitations, in this work PBF-LB/M is used to manufacture the tooth geometry close to the target on a flat sheet. Subsequently, the three-dimensional part geometry is realized by forming. The advantage is that the orbital forming step is not necessary. With that, the tooth geometry does not depend on material flow. A further benefit is geometric flexibility of additive manufacturing processes. Hence, diversity of variations can be increased over a wide range without additional cost intensive forming tools for each single part geometry. Besides, the potentials and challenges of the approach are discussed. The investigations include characterization of formability of sheet metal and AM material, metallographic analysis and hardness measurement. A process chain for manufacturing hybrid parts is presented and the final part geometry is evaluated by topography measurement. The major finding is that the tooth geometry manufactured by additive manufacturing and forming is closer to the target than for the conventional process chain. Additionally, a comparison of technological and economic advantages is drawn. Finally, an extension of the approach is presented by hybrid parts with additively manufactured structures on both sides of the sheet metal.<br
Keywords: Forming; Additive manufacturing; Process combination; Hybrid part

A non-invasive form finding approach with application to metal forming - Landkammer, Philipp; Schneider, Thomas; Schulte, Robert Karl; Steinmann, Paul; Merklein, Marion (Production Engineering, 2016)
Inverse form finding aims in determining the optimal material configuration of a workpiece for a specific forming process. A gradient- and parameter-free (nodal-based) form finding approach has recently been developed, which can be coupled non-invasively as a black box to arbitrary finite element software. Additionally the algorithm is independent from the constitutive behavior. Consequently, the user has not to struggle with the underlying optimization theory behind. Benchmark tests showed already that the approach works robustly and efficiently. This contribution demonstrates that the optimization algorithm is also applicable to more sophisticated forming processes including orthotropic large strain plasticity, combined hardening and frictional contact. A cup deep drawing process with solid-shell elements and a combined deep drawing and upsetting process to form a functional component with external teeth are investigated.
LFT Import::2019-08-07 (2148)
Keywords: Inverse form finding; Shape optimization; Cup deep drawing; Sheet-bulk Metal Forming

Augmented Reality for Forming Technology - Visualisation of Simulation Results and Component Measurement - Lechner, Michael; Schulte, Robert Karl; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2019)
In sheet and bulk forming, numerical simulation has become established over the last 20 years as an indispensable tool for research and industrial practice. The numerical calculation of forming processes supports a time- and cost-efficient development in the context of a virtual product evaluation. Currently, simulation and measurement results are mainly displayed on conventional screens. However, this approach has several disadvantages. On the one hand, only cut-outs can be displayed, especially in the case of large components. A visualisation of entire components in real size is often not possible. On the other hand, no direct comparison with the real components is possible. Augmented Reality is a promising approach to solve the challenges outlined above. As part of the contribution, an innovative approach for component validation based on Augmented Reality technology will be introduced. Thereby, the visualisation using different Augmented Reality devices and the feasibility of a measurement task with Augmented Reality devices will be presented.
CRIS-Team Scopus Importer:2020-02-21

Augmented Reality Technology for the Purpose of Sheet Metal Forming Simulation Evaluation - Lechner, Michael; Schulte, Robert Karl; Meckler, S.; Merklein, Marion (10th Forming Technology Forum 2017 - Model Based Control for Smart Forming Processes, 2017)
LFT Import::2019-08-05 (2276)

Comparison of Strain-path Indicators for Analysis of Processes in Sheet-bulk Metal Forming - Gutknecht, Florian; Vogel, Manfred; Schulte, Robert Karl; Merklein, Marion; Rosenbusch, Daniel; Koch, Sergej; Hübner, Sven; Behrens, Bernd Arno; Tekkaya, Erman; Clausmeyer, Till (The 13th International Conference on Numerical Methods in Industrial Forming Processes, 2019)

Control of the material flow in sheet-bulk metal forming using modifications of the tool surface - Löffler, Maria; Schulte, Robert Karl; Freiburg, D.; Biermann, Dirk; Stangier, D.; Tillmann, W.; Merklein, Marion (International Journal of Material Forming, 2019)
Sheet-bulk metal forming (SBMF) processes are characterized by a successive and/or simultaneous occurrence of different load conditions such as the stress and strain states. These conditions influence the material flow and often lead to a reduced geometrical accuracy of the produced components. To improve the product quality, a control of the material flow is required. One suitable approach, the local adaption of tribological conditions by means of surface modifications of tool or workpiece, so-called tailored surfaces. To control the material flow and thus to improve the component accuracy, methods to reduce and to increase friction are needed. The aim of this study is to determine requirements for necessary adaptions of the friction, the identification of tribological mechanisms for different types of tool-sided tailored surfaces as well as the verification of the effectiveness of these surface modifications to improve the results of a specific SBMF process. The numerical analysis of a combined deep drawing and upsetting process revealed that this process is characterized by two areas of varying tribological load conditions. Using a numerical analysis, the friction factor gradient between these two areas was identified as a main influencing factor on the material flow. Based on this finding, Chromium-based hard coatings for the reduction of the friction and high-feed milled surfaces for an increase of the friction were investigated regarding their frictional behaviour. The results of the ring-compression tests revealed that the carbon content and the post treatment of coated tool surfaces are relevant to reduce the friction. The increased profile depth of the milled surfaces was identified as the main influencing factor on the tribological behaviour of this kind of tailored surfaces. The effectiveness of both types of tailored surfaces was verified for the combined deep drawing and upsetting process.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Coating; Milling; Sheet-Bulk Metal Forming; Surface Modification; Tribology

Data-Based Control of A Multi-Step Forming Process - Schulte, Robert Karl; Frey, Philipp; Hildenbrand, Philipp; Vogel, Manfred; Betz, C.; Lechner, Michael; Merklein, Marion (Proc. International Deep Drawing Research Group Conf. IDDRG 2017, 2017)
LFT Import::2019-08-05 (2253)

Data-driven Model Development for Quality Prediction in Forming Technology - Kirchen, Iris; Vogel-Heuser, Birgit; Hildenbrand, Philipp; Schulte, Robert Karl; Vogel, Manfred; Lechner, Michael; Merklein, Marion (15th IEEE International Conference on Industrial Informatics (INDIN), 2017)
this investigation data recorded from a flexible rolling process is processed by data driven methods to develop a quality prediction model for manufactured blanks. A concept for an incremental prediction method is proposed, which takes into account the specific character of the discrete manufacturing process. The method is evaluated based on a data set of process and quality data provided by a test rig. By the example of a specific quality parameter the effectiveness of the proposed method is confirmed. A precise quality prediction model is developed, which predicts the quality value with a high accuracy.
LFT Import::2019-08-05 (2252)
Keywords: automated Production Systems; data analytics; quality prediction

Designing, manufacturing and processing of Tailored Blanks in a sheet-bulk metal forming process - Schulte, Robert Karl; Hildenbrand, Philipp; Lechner, Michael; Merklein, Marion (45th SME North American Manufacturing Research Conference, NAMRC 45, LA, USA, 2017)
Sheet-bulk metal forming is an innovative method for the manufacturing of functional components by applying bulk metal forming processes or combined sheet and bulk metal forming processes to sheet metal. The investigated process combines deep drawing and upsetting. Occurring 2D and 3D stress and strain states lead to challenges regarding the material flow control during the forming process to ensure a high die filling and accurate part geometry. Regarding these challenges, the application of conventional semi-finished products is not expedient wherefore Tailored Blanks with a process adapted sheet thickness distribution are applied to the forming process. The Tailored Blank geometry is designed by a numerical analysis and manufactured by an orbital forming process considering the resulting geometric part properties during deep drawing and upsetting. Therefore, the whole process chain from the conventional circular blank to the finished functional component is linked and modelled. This enables a realistic description of the part properties as the effective plastic strain caused in the manufacturing of semi-finished products is taken into account in the processing of the material. Subsequently the results are verified by experimental tests.
LFT Import::2019-08-05 (2231)
Keywords: Deep drawing; Finite element method (FEM); Forming; Sheet metal

Fringe projection profilometry in production metrology: A multi-scale comparison in sheet-bulk metal forming - Hinz, Lennart; Metzner, Sebastian; Müller, Philipp; Schulte, Robert Karl; Besserer, Hans-Bernward; Wackenrohr, Steffen; Sauer, Christopher; Kästner, Markus; Hausotte, Tino; Hübner, Sven; Nuernberger, Florian; Schleich, Benjamin; et al. (Sensors, 2021)
Fringe projection profilometry in combination with other optical measuring technologies has established itself over the last decades as an essential complement to conventional, tactile measuring devices. The non-contact, holistic reconstruction of complex geometries within fractions of a second in conjunction with the lightweight and transportable sensor design open up many fields of application in production metrology. Furthermore, triangulation-based measuring principles feature good scalability, which has led to 3D scanners for various scale ranges. Innovative and modern production processes, such as sheet-bulk metal forming, thus, utilize fringe projection profilometry in many respects to monitor the process, quantify possible wear and improve production technology. Therefore, it is essential to identify the appropriate 3D scanner for each application and to properly evaluate the acquired data. Through precise knowledge of the measurement volume and the relative uncertainty with respect to the specimen and scanner position, adapted measurement strategies and integrated production concepts can be realized. Although there are extensive industrial standards and guidelines for the quantification of sensor performance, evaluation and tolerancing is mainly global and can, therefore, neither provide assistance in the correct, application-specific positioning and alignment of the sensor nor reflect the local characteristics within the measuring volume. Therefore, this article compares fringe projection systems across various scale ranges by positioning and scanning a calibrated sphere in a high resolution grid.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Coordinate metrology; Fringe projection; Production metrology; Sheet-bulk metal forming

Functional Analysis of Components Manufactured by a Sheet-Bulk Metal Forming Process - Hetzel, Andreas; Schulte, Robert Karl; Vogel, Manfred; Lechner, Michael; Besserer, Hans-Bernward; Maier, Hans Juergen; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2021)
Due to rising demands regarding the functionality and load-bearing capacity of functional components such as synchronizer rings in gear systems, conventional forming operations are reaching their limits with respect to formability and efficiency. One way to meet these challenges is the application of the innovative process class of sheet-bulk metal forming (SBMF). By applying bulk forming operations to sheet metal, the advantages of both process classes can be combined, thus realizing an optimized part weight and an adapted load-bearing capacity. Different approaches to manufacturing relevant part geometries were presented and evaluated regarding the process properties and applicability. In this contribution, a self-learning engineering workbench was used to provide geometry-based data regarding a novel component geometry with circumferential involute gearing manufactured in an SBMF process combination of deep drawing and upsetting. Within the comprehensive investigations, the mechanical and geometrical properties of the part were analyzed. Moreover, the manufactured components were compared regarding the increased fatigue strength in cyclic load tests. With the gained experimental and numerical data, the workbench was used for the first time to generate the desired component as a CAD model, as well as to derive design guidelines referring to the investigated properties and fatigue behavior.<br
Keywords: sheet-bulk metal forming; mechanical properties; self-learning engineering workbench; functional behavior; fatigue life modeling; Z-integral approach

Fundamental analysis For the application of hybrid semi-finished products in sheet-bulk metal forming - Schulte, Robert Karl; Lechner, Michael; Merklein, Marion (Journal of Materials Processing Technology, 2020)
Sheet-bulk metal forming is an expedient approach to efficiently manufacture functional components out of sheet metal. In order to reduce weight of the component manufactured, an application-adapted approach was developed to replace the conventional steel blank by a semi-finished product consisting of two blanks with half the thickness to enable the tailored combination of different materials in a combined deep drawing and upsetting process. To establish a basis for the application of these hybrid semi-finished products, first of all multilayer steel semi-finished products are drawn and upset in the process combination. Thereby, the upsetting process induces a three dimensional material flow and at the same time an interlocking connection of the two blanks. The gained results are the transferred onto the combination of steel and aluminium alloys within one semi-finished product. Fundamental dependencies as well as the influence of the application of different steel grades are investigated.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Metal forming; Sheet metal; Simulation

Innovative approaches for controlling the material flow in sheet-bulk metal forming processes - Merklein, Marion; Lechner, Michael; Gröbel, Daniel; Löffler, Maria; Schneider, Thomas; Schulte, Robert Karl; Hildenbrand, Philipp (Manufacturing Review, 2016)
Using sheet-bulk metal forming processes the application of bulk forming operations on sheet metals enables the manufacturing of functional components with local wall thickness variations. As these processes come along with a two- and three-dimensional material flow, the control of the material flow is crucial for ensuring a proper filling of functional elements and thus ensuring the components quality. Controlling the material flow can be achieved by different solutions: the local adaption of tribological conditions and the application of process adapted semi-finished parts. In this paper, both solutions as well as their general qualification in two sheet-bulk metal forming processes are presented.
LFT Import::2019-07-29 (2144)
Keywords: Forming; Material flow; Processes

Interaction of various functional elements in thin-walled cups formed by a sheet-bulk metal forming process - Schulte, Robert Karl; Schneider, Thomas; Lechner, Michael; Merklein, Marion (NUMIFORM 2016: The 12th International Conference on Numerical Methods in Industrial Forming Processes, 2016)
Sheet-bulk metal forming allows the manufacturing of sheet metal parts with integrated functional elements. The investigated process combines deep drawing and upsetting. The occurring 2D and 3D stress and strain states lead to challenges regarding material flow control due to different geometries of functional elements. The numerical analysis shows the transferability for the results of the different functional elements for their combination and the interaction between those functional elements regarding the material flow. The results are validated by experimental tests.
LFT Import::2019-08-05 (2202)

Investigation of tailored tool surfaces for improving the component quality of sheet-bulk metal forming parts produced by a combined deep-drawing and upsetting process - Henneberg, Johannes; Schulte, Robert Karl; Merklein, Marion (SCT Conference Proceedings, 2022)
Nowadays the automotive industry is confronted with increasing demands for lightweight components with integrated functional elements, as they are for instance used as synchronizers in gearboxes. Established manufacturing processes like sheet metal forming are limited producing such parts. Therefore, the innovative manufacturing technology sheet-bulk metal forming is investigated. By the application of bulk forming operations to sheet metals, functionally integrated parts can be produced in an efficient way. In this research, a combined deep-drawing and upsetting process is analyzed to form components with involute external gears. The reduced die filling of the gears is identified as a major challenge. Consequently, this research aims to increase the die filling of the gears through tool-sided adaptions. For analyzing the cause of the reduced die filling, a numerical process model is built up and validated. By analyzing this model, an undesired material flow from the functional elements to the center of the part is identified. In a next step, the potential of material flow control by global and local adaptation of the friction is numerically investigated. For this, the friction factor is varied between 0.1 and 0.5 in different areas. The numerical results indicate that by locally adjusting the friction, the material flow can be controlled and thus the shape of the gearing can be improved. Based on the numerical findings, tailored friction systems are implemented in an experimental setup. The tool surfaces are locally modified by an abrasive blasting process. Hereby, the friction is tailored according to the numerically determined requirements. Concluding, the applicability of tailored tool surfaces for material flow control and improvement of component quality is experimentally show
Keywords: Cold forming; Tribology; Surface modification; Material flow control; Numerical simulation; Lightweight design; Steel

Investigations of ductile damage during the process chains of toothed functional components manufactured by sheet-bulk metal forming - Isik, Kerim; Gerstein, Gregory; Schneider, Thomas; Schulte, Robert Karl; Rosenbusch, Daniel; Clausmeyer, Till; Nuernberger, Florian; Vucetic, Milan; Koch, Sergej; Huebner, Sven; Behrens, Bernd-Arno; Tekkaya, A. Erman; et al. (Production Engineering, 2016)
Sheet-bulk metal forming processes combine conventional sheet forming processes with bulk forming of sheet semi-finished parts. In these processes the sheets undergo complex forming histories. Due to in- and out-of-plane material flow and large accumulated plastic strains, the conventional failure prediction methods for sheet metal forming such as forming limit curve fall short. As a remedy, damage models can be applied to model damage evolution during those processes. In this study, damage evolution during the production of two different toothed components from DC04 steel is investigated. In both setups, a deep drawn cup is upset to form a circumferential gearing. However, the two final products have different dimensions and forming histories. Due to combined deep drawing and upsetting processes, the material flow on the cup walls is three-dimensional and non-proportional. In this study, the numerical and experimental investigations for those parts are presented and compared. Damage evolution in the process chains is simulated with a Lemaitre damage criterion. Microstructural analysis by scanning electron microscopy is performed in the regions with high mechanical loading. It is observed that the evolution of voids in terms of void volume fraction is strongly dependent on the deformation path. The comparison of simulation results with microstructural data shows that the void volume fraction decreases in the upsetting stage after an initial increase in the drawing stage. Moreover, the concurrent numerical and microstructural analysis provides evidence that the void volume fraction decreases during compression in sheet-bulk metal forming.
LFT Import::2019-07-29 (2147)
Keywords: FE simulation; Lemaitre damage model; Sheet-bulk metal forming

Manufacturing of functional elements by sheet-bulk metal forming processes - Gröbel, Daniel; Schulte, Robert Karl; Hildenbrand, Philipp; Lechner, Michael; Engel, Ulf; Sieczkarek, P.; Wernicke, Sebastian; Gies, Soeren; Tekkaya, A. E.; Behrens, B. A.; Huebner, S.; Vucetic, M.; et al. (Production Engineering, 2016)
Due to increasing economic and ecological restrictions, conventional sheet and bulk forming operations often reach their limits with regard to part weight and functional integration. One solution to meet those challenges is provided by sheet-bulk metal forming (SBMF) processes. SBMF is defined as the application of bulk forming operations on sheet metal. SBMF can be combined with conventional sheet forming operations and offers the opportunity to form highly functional integrated parts out of sheet metal. It contains the benefit of an optimization of the part weight and a shortening of the process chain. Recent research has found different solutions regarding the actual implementation of SBMF in several process variants. In this paper, a categorisation for functional elements on sheet metal parts is proposed. A selection of possible approaches for their manufacturing is presented. The process variants are compared by means of the main process characteristics. By these means, the choice of a suitable option shall be facilitated for practical manufacturing design and for a particular relevant product.
LFT Import::2019-07-29 (2152)
Keywords: Flow control; Sheet-bulk metal forming; Tailored blanks; Tailored surfaces

Manufacturing of tailored blanks by flexible rolling and its application in a sheet-bulk metal forming process - Vogel, Manfred; Lechner, Michael; Hildenbrand, Philipp; Schulte, Robert Karl; Merklein, Marion (Proceedings SCT2017, 2017)
LFT Import::2019-08-05 (2229)

Manufacturing of Tailored Blanks with Pre-shaped Involute Gearings by Using a Flexible Rolling Process and Its Application in a Sheet–Bulk Metal Forming Process - Vogel, Manfred; Schulte, Robert Karl; Kaya, Onur; Merklein, Marion (Forming the Future - Proceedings of the 13th International Conference on the Technology of Plasticity, 2021)
Nowadays, the efficient manufacturing of functional components in short process chains is important due to the goal of a further reduction of greenhouse gases. Additionally, there are also technical demands like functional integration combined with an improvement of the component’s properties. Previous investigations have shown that the application of tailored blanksTailored blank with a defined thickness profile can lead to an improvement of the geometrical and mechanical properties of functional components. However, common forming processes reach their limits. A promising approach to enlarge these process limits is the application of bulk forming operations to sheet metals, the so-called sheet–bulk metal forming (SBMF). Within this process class, one possibility for manufacturing such blanks is a flexible rollingFlexible rolling process. As a result of movement of two rolling tools in combination with a die cavity in the lower tool, a defined geometry can be manufactured perpendicular to the sheet plane. In order to raise the complexity combined with a shorter process chain and thus to fulfil the requirements defined by the subsequent forming operations, a new design that contains a preform of involute gearings is introduced. In order to acquire process knowledge, the mild deep drawing steel DC04 with an initial sheet thickness of t0 = 2.0 mm is used. Furthermore, the subsequent application of the tailored blanks in a combined deep drawing and upsetting process is shown, with a characterization of the geometrical and mechanical properties.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Flexible rolling; Sheet forming; Tailored blank

Maßgeschneiderte Halbzeuge - Umformtechnische Herstellung von Funktionsbauteilen zur Realisierung von Leichtbaukomponenten - Hetzel, Andreas; Schulte, Robert Karl; Vogel, Manfred; Degner, Julia; Merklein, Marion (wt Werkstattstechnik - Online, 2019)
Sheet Bulk Metal Forming enables the efficient manufacturing of functional lightweight components with different functional elements in a combined single stage deep drawing and upsetting process. By investigating the forming results with a conventional blank, regarding the properties like grain structure and Vickers hardness distribution, process limitations such as buckling and folding can be detected. These failures occur due to a three-dimensional stress and strain state as well as an insufficient die filling. A significant improvement of the quality of the produced parts can be enabled by the use of Tailored Blanks in the investigated process chain. With the manufacturing of the semi-finished parts by orbital forming, an adapted material pre-distribution can be realized, thus improving the die filling followed by a decrease of the parts' failures. Current research at the Institute of Manufacturing Technology focuses on the extension of the applicability of Tailored Blanks.
CRIS-Team Scopus Importer:2020-02-21

New process strategies to manufacture tailored blanks out of DP600 by orbital forming - Hildenbrand, Philipp; Schulte, Robert Karl; Merklein, Marion (Applied Mechanics and Materials, 2015)
LFT Import::2019-07-29 (2115)

Process Combination for the Manufacturing of Toothed, Thin-Walled Functional Elements by Using Process Adapted Semi-finished Products - Vogel, Manfred; Schulte, Robert Karl; Lechner, Michael; Merklein, Marion (Springer International Publishing, 2021)
The scientific objective is the analysis of a process combination for the manufacturing of toothed, thin-walled functional elements from process-optimized semi-finished products. By using an upsetting, orbital forming as well as a modified flexible rolling process, tailored blanks with flow-optimized properties are manufactured. In this context, a defined material flow control plays a decisive role for the forming of different geometries. In order to pursue a holistic approach, the process limits as well as the potential of the individual processes are identified. With the application of such blanks, geometrically complex components with functional elements such as gears or carriers are formed in a new combined deep-drawing and upsetting process. The aim is to reduce the number of steps in the process chain and thus save energy and resources. Thereby, different levels of functional integration are taken into account with regard to the geometry and arrangement of the functional elements, but also combinations of both.

Tribological measures for controlling material flow in sheet-bulk metal forming - Löffler, Maria; Andreas, Kolja; Engel, Ulf; Schulte, Robert Karl; Gröbel, Daniel; Krebs, Eugen; Freiburg, Dennis; Biermann, Dirk; Stangier, Dominic; Tillmann, Wolfgang; Weikert, Tim; Wartzack, Sandro; et al. (Production Engineering, 2016)
Sheet-bulk metal forming (SBMF) is characterized by successive and/or simultaneous occurrence of quite different load conditions regarding stress and strain states. These conditions significantly influence the material flow and thus the geometrical accuracy of the components. To improve the product quality a control of the material flow is required. An appropriate approach is given by locally adapted tribological conditions due to surface modifications of tool and workpiece, so-called tailored surfaces. Within the present study different methods to adapt the surfaces are presented and investigated with respect to their tribological effectiveness in SBMF. In a first step, requirements regarding necessary adaptions of the friction values for two SBMF processes are numerically defined. Based on the requirements different tailored surfaces are presented and analyzed regarding their tribological influence. Finally, the potential of surface modifications to improve SBMF processes is shown.
Keywords: Tribology; Surface modification; Sheet-bulk metal forming

Umformtechnische Herstellung von Funktionsbauteilen aus Tailored Blanks durch Blechmassivumformverfahren - Schulte, Robert Karl; Lechner, Michael; Vogel, Manfred; Hildenbrand, Philipp; Merklein, Marion (22. Umformtechnisches Kolloquium Hannover – Innovationspotentiale in der Umformtechnik. 15./16.03.2017, 2017)
LFT Import::2019-08-05 (2230)

Verfahrenskombination zur umformtechnischen Herstellung von verzahnten, dünnwandigen Funktionselementen aus prozessoptimierten Halbzeugen - Vogel, Manfred; Schulte, Robert Karl; Hetzel, Andreas; Lechner, Michael; Merklein, Marion (Aktuelle Entwicklungen im Bereich der Umformtechnik - 23. Umformtechnisches Kolloquium Hannover, 2020)
Konventionelle Blech- und Massivumformverfahren stoßen heute insbesondere im Automobilbereich, bedingt durch stetig steigende Ansprüche an Ressourceneffizienz und Funktionsintegration, oft an ihre Grenzen. Die Forderung nach verkürzten Prozessketten erhöht den Bedarf nach einer Erweiterung bestehender Prozessgrenzen zusätzlich. Ein Ansatz zur Bewältigung dieser Herausforderungen ist der Einsatz der innovativen Prozessklasse der Blechmassivumformung (BMU), welche durch die Anwendung von Massivumformoperationen auf Blechhalbzeuge definiert ist. Charakteristisch für diese Prozessklasse ist das Auftreten von dreidimensionalen Spannungs- und Dehnungszuständen, welche sowohl ein Ausdünnen als auch ein Aufdicken der Ausgangsplatine zulassen. Um die angestrebten Bauteileigenschaften realisieren zu können, ist der Aufbau eines grundlegen Prozessverständnisses zur gezielten Steuerung des Materialflusses unumgänglich. Für eine Steigerung der Materialflusskontrolle sowie einer Verbesserung der Bauteileigenschaften, werden im Teilprojekt A1 des Sonderforschungsbereiches Transregio 73 prozessangepasste Halbzeuge ausgelegt, umformtechnisch gefertigt und zu Funktionsbauteilen weiterverarbeitet. Die Halbzeugherstellung erfolgt dabei auf zwei unterschiedlichen Prozessrouten. Einsatz finden hierfür ein flexibler Walzprozess, sowie ein Taumelprozess, welche die Herstellung von Halbzeugen mit gradierten geometrischen und mechanischen Eigenschaften erlauben. Diese werden anschließend einstufigen Verfahrenskombination aus Tiefziehen und Stauchen zu Bauteilen mit Verzahnungs- und Mitnehmerelementen umgeformt. Wesentliche grundlagenwissenschaftliche Erkenntnisse des Projekts werden aktuell im Transferprojekt T02 zusammen mit Projektpartnern aus der Industrie in die Anwendung übertragen